Introducing second language acquisition - Saville-Troike, Muriel , 1936- (Cambridge introductions to language and linguistics, 2012)
"Written for students encountering the topic for the first time, this is a clear and practical introduction to second language acquisition (SLA). Using non-technical language it explains how a second language is acquired; what the learner of a second language needs to know; and why some learners are more successful than others. This new edition of Muriel Saville-Troike's bestselling textbook introduces in a step-by-step fashion a range of fundamental concepts, such as SLA in adults and children, in formal and informal learning contexts, and in diverse sociocultural settings. Taking an interdisciplinary approach, it encourages students to consider SLA from linguistic, psychological, and social perspectives. Providing a solid foundation in SLA, this book has become the leading introduction to the field for students of linguistics, psychology, education, and trainee language teachers" -- Provided by publisher